Peningkatan Pemahaman Mahasiswa Blok Keperawatan Jiwa Melalui Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Divisions) Pada Materi Terapi Modalitas Keperawatan Jiwa - Tutu April Ariani (Journal of Ners and Midwifery, 2019)
Upaya yang dilakukan untuk meningkatkan kemampuan berpikir kritis yaitu dengan menerapkan model pembelajaran yang dipandang akomodatif bagi peningkatan kemampuan berpikir kritis mahasiswa maupun aktivitas belajar, yaitu  dengan  menerapkan  model  pembelajaran  kooperatif.  Tipe-tipe pembelajaran kooperatif diantaranya adalah Metode STAD (Student Teams- Achievement Divisions). Penelitian tindakan kelas ini dilaksanakan di Se- mester III Prodi S1 Keperawatan FIKES Universitas Muhammadiyah Malang, Kelas A. Kondisi  lain yang terikat bahwa latar belakang  mereka cukup beragam,mereka terdiri dari beragam suku, tempat asal, sehingga secara keseluruhan Semester III relatif cukup heterogen. Pengamatan dari ceklist merupakan data utama yang mengamati aspek: bekerjasama, menyampaikan gagasan, bertanya, memperhatikan pertanyaan teman, menanggapi, mampu mngerti secara mendalam tentang materi, berperan aktif dalam kelompok, dapat menjadi penengah, menjelaskan, menarik kesimpulan materi. Penelitian tindakan memiliki 4 tahapan yaitu: planning, doing action, observation dan reflection, yang berjalan melalui 2 siklus/ putaran (setiap putaran dilakukan 2 kali pertemuan). Tahap terakhir dari proses ini adalah: Reflection. Hasil dari observasi  diorganisir  dan  dianalisis.  Tahap  ini  dapat  digunakan  oleh instruktur  untuk  memberikan  umpan  balik  berdasar  hasil  pengamatan. Berikutnya didiskusikan tindakan yang sudah sesuai untuk meningkatkan pemahaman mahasiswa di mata kuliah Keperawatan Kesehatan Jiwa.  Many ways can improve to critical thinking skills of student  are applying learning  models  that  are  considered  accommodative  for  improving  stu- dents’ critical thinking skills and learning activities by applying coopera- tive learning models. The types of cooperative learning include the STAD Method (Student Teams-Achievement Divisions). This action research was conducted in one class of third semester  in Bachelor Graduate  Nursing Program Study FIKES at the University of Muhammadiyah Malang, espe- cially  Class  A.  Other  conditions  that  were  bound  were  that  their  back- grounds were quite diverse, they consisted of various tribes, places of ori- gin, so that overall Semester III was relatively heterogeneous. Data col- lected by observation sheets, among others, were observed: cooperation in groups,  gave  ideas,  asked  questions,  pay  attention  to  friend  questions, gave  responses, ability  to  understand  material, participation  in  groups, ability  to mediate  if  there are  groups who  misunderstand,  ability to  ex- plain and conclude material discussed. The action through 4 stages, are respectively: planning, action, observation, and reflection, carried out in two cycles (each cycle carried out twice meeting). The final stage of this process is Reflection. The results obtained in the observation phase are collected  and  analyzed.  At  this  stage,  the  instructor  can  reflect  on  the results  of  observations  and  discussions  to  examine  whether  the  actions taken can improve students’ understanding of the Mental Health Nursing course. The results of data analysts carried out in stages will be used as a reference for planning the next cycle.  The results showed  a decrease in misunderstanding,  there  were  3  people (11.11%)  out  of  27  students  who did not reach comprehension of competency, because the accumulation of values   <80. There was an increase in the passing of the competency test to 19 people (88.89%) with the above scores 80.00. It is expected that this STAD method can be applied to other subjects so that overall competency test graduation increases.